Water use efficiency, plant growth and vegetative traits of rubber (Hevea brasiliensis) seedlings grown using different growing media and water levels - Salisu, Monsuru Adekunle; Sulaiman, Zulkefly; Che Rus, Ridzwan; A. Samad, Mohd Yusoff; Usaizan, Norhanizan; Oladosu, Yusuff; Paiman, . (Southern Cross Journals, 2020)
The aim of this study was to evaluate the effects of soilless media and water levels on growth and physiological response of rubber plant. The four water levels were I50: 50%, I75: 75%, I100: 100% and I150: 150%) with three replications per water treatment and four soilless media. Water levels were determined as irrigation needed for the root zone in growing media to rise to field capacity I100:100%, at field capacity (FC). The experiment was laid out in randomized complete block design (RCBD) in factorial arrangement 3 x 4 with three replications. Soilless medium contains proportion of vermiculite, perlite, coconut husk, empty fruit bunch (EFB) compose, Christmas Island Rock Phosphate (CIRP), peat moss, urea-N and burnt rice husk coded as M1. Vermiculite, perlite, coconut husk, EFB, CIRP, peat moss, urea-N, sugarcane bagasse coded as M2. M3 is a commercial soilless medium and 100% soil was designated as control. The M1 significantly influenced almost all plant growth traits, noticeable in biomass production. Growth of plants in M1 corresponded to higher water use efficiency WUEinstantaneous and WUEintrinsic, the M1 increased plant growth like LAR, biomass production and root morphological traits. Shoot dry weight of the plant was greater (14.66 g/plant) when 150% was applied and significantly different from M2 (10.36 g/plant), M3 (4.73 g/plant) and M4 6.22 g/plant. Lower water level 50%, applied in plant grown in M1 (31.94 g/plant) recorded highest total shoot fresh weight (SFW). The results showed suitability of the soilless medium M1 and the 50% water level for rubber nursery planting. Consequently, it is recommended for planting where management and control of irrigation water are considered necessary in rubber plantation.